Efficient Homologous RNA Recombination and Requirement for an Open Reading Frame during Replication of Equine Arteritis Virus Defective Interfering RNAs - Molenkamp, Richard (American Society for Microbiology, 2000)
Equine arteritis virus (EAV), the prototype arterivirus, is an enveloped plus-strand RNA virus with a genome of approximately 13 kb. Based on similarities in genome organization and protein expression, the arteriviruses have recently been grouped together with the coronaviruses and toroviruses in the newly established order Nidovirales. Previously, we reported the construction of pEDI, a full-length cDNA copy of EAV DI-b, a natural defective interfering (DI) RNA of 5.6 kb (R. Molenkamp et al., J. Virol. 74:3156–3165, 2000). EDI RNA consists of three noncontiguous parts of the EAV genome fused in frame with respect to the replicase gene. As a result, EDI RNA contains a truncated replicase open reading frame (EDI-ORF) and encodes a truncated replicase polyprotein. Since some coronavirus DI RNAs require the presence of an ORF for their efficient propagation, we have analyzed the importance of the EDI-ORF in EDI RNA replication. The EDI-ORF was disrupted at different positions by the introduction of frameshift mutations. These were found either to block DI RNA replication completely or to be removed within one virus passage, probably due to homologous recombination with the helper virus genome. Using recombination assays based on EDI RNA and full-length EAV genomes containing specific mutations, the rates of homologous RNA recombination in the 3′- and 5′-proximal regions of the EAV genome were studied. Remarkably, the recombination frequency in the 5′-proximal region was found to be approximately 100-fold lower than that in the 3′-proximal part of the genome.